Telephone Follow-Up After Cardiac Surgery: A Strategy to Reduce Readmissions and Unnecessary Emergency Visits - Gautam, Navin Chandra; Joshi, Rheecha; Joshi, Dharmendra; Thakur, Apurba; Jha, Vivek; Basnet, Nishesh; Pokhrel, Biswo; Poudel, Sabin; Dhakal, Prakrit; Upreti, Gaurav; Rajbanshi, Bijoy Gopal (Nepalese Heart Journal, 2026)
Hospital readmission after cardiac surgery imposes substantial clinical and financial burdens, particularly in resource-limited countries such as Nepal. Recurrent readmissions and unnecessary emergency visits create significant emotional, physical, and economic stress for patients and caregivers while increasing healthcare utilization and hospital stay. Inadequate discharge counselling and incomplete understanding of postoperative instructions further contribute to high revisit rates. Structured telephone follow-up may provide a simple and cost-effective strategy to bridge the gap between hospital discharge and recovery. It can reinforce adherence to medications, facilitate early identification of warning signs, and help to prevent avoidable emergency visits. International evidence supports its role in improving patient satisfaction and reducing readmissions. However, evidence from South Asia remains limited. Tailored implementation of structured telephone follow-up may serve as a practical strategy to improve postoperative outcomes after cardiac surgery in Nepal.